ANALYSIS OF STUDENT RESPONSES TO USE MAGIC BAG CONSTRUCTION MEDIA SPACE FOR CLASS V SD - Antina Tri Mupida; Dwi Kameluh A; Ida Putri Rarasati (Universitas Islam Balitar, 2019)
Based on observations and interviews conducted by the researchers found that teachers only use whiteboard media so as to make the students less active in learning, and the acquisition value of mathematics learners are still low. This study aims to develop learning media in the form of Build Space Magic Pockets that can be used as an effective medium in elementary school mathematics classroom.This study uses the Research and Development approach or Research and Development (R & D), which is directed at the development of geometrical magic pocket media for elementary school mathematics classroom. Step in this research was conducted through six stages: 1. Observation, 2. Planning Product Design, 3. Validation Expert, 4. Revision 5. Simulation Instructional, 6. Evaluation and Results, 7. Publications. Methods of data analysis in this study is a qualitative and quantitative approach. Learning media in the form of Pockets Magic Build Space that has been developed has been tested through a questionnaire validated by the validation results of the expert content of 94%, media experts, 83%, and for the acquisition of the validation results linguists still 83% of the three results of this validation media magic bag geometrical entered at a very decent qualifying, nothing needs to be revised. Based on the results of questionnaire responses of learners to wake magic pocket media room 258 the number of results obtained with the maximum number of results obtained 260 and the percentage 99% means media magic bag geometrical get a positive response from students. Magic bag so that the media can be used to wake space grade elementary school mathematics.